DEVELOPMENT OF MATHEMATHICS STORYBOOK FOR CHILD GROUP B IN TK NEGERI PEMBINA SOUTH INDRALAYA - Syafdaningsih Syafdaningsih; Ria Rosidah (UPI Kampus Cibiru, 2018)
Abstract: Research development has a view to produce story books mathematics. The development of story books mathematics it uses combination model of rowntree and evaluation tessmer. Model of rowntree consists of three stages, in the planning, developmental stage and the evaluation. At the evaluation an evaluation formative presented by tessmer consisting of five stage, in the self evaluation, experts review, one-to-one evaluation, small group evaluation and field test. Using techniques data collection observation. From the experts review obtained the average score the assessment of the experts on the Book 1 of 3,90% (category very valid), Book 2 of 3,90% (category very valid), Book 3 of 3,90% (category very valid), Book 4 of 3,90% (category very valid). Phase one-to-one evaluation obtained the average observations children with Book 1 of 85% (category very good), Book 2 of 86% (category very good), Book 3 of 87% (category very good), and Book 4 of 86% (category very good). The small group evaluaion obtained the average observation on the Book 1 of 88% (category very good), Books 2 of 90% (category very good), Book 3 of 91% (category very good), and Book 4 of 92% (category very good). At the field for observation test scores on the Book 1 of 95% (category very good), Books 2 of 95% (category very good), Book 3 of 91% (category very good), Books 4 of 95% (category very good). Of all stages already done so it can be concluded that story books mathematics expressed valid, practical, and have an effect potential for children.Keyword: story books, mathematics Abstrak: Pengembangan penelitian ini memiliki pandangan untuk menghasilkan buku-buku cerita matematika. Pengembangan buku cerita matematika menggunakan kombinasi model rowntree dan evaluasi tessmer. Model rowntree terdiri dari tiga tahap, dalam tahap perencanaan, tahap pengembangan dan evaluasi. Pada evaluasi evaluasi formatif yang disajikan oleh tessmer yang terdiri dari lima tahap, dalam evaluasi diri, ulasan ahli, evaluasi satu-ke-satu, evaluasi kelompok kecil dan uji lapangan. Menggunakan teknik observasi pengumpulan data. Dari tinjauan ahli diperoleh skor rata-rata penilaian ahli pada Buku 1 sebesar 3,90% (kategori sangat berlaku), Buku 2 dari 3,90% (kategori sangat valid), Buku 3 dari 3,90% (kategori sangat valid), Buku 4 dari 3,90% (kategori sangat valid). Tahap satu-ke-satu evaluasi diperoleh rata-rata pengamatan anak-anak dengan Buku 1 dari 85% (kategori sangat baik), Buku 2 dari 86% (kategori sangat baik), Buku 3 dari 87% (kategori sangat baik), dan Buku 4 dari 86% (kategori sangat bagus). Evaluasi kelompok kecil memperoleh rata-rata pengamatan pada Buku 1 88% (kategori sangat baik), Buku 2 dari 90% (kategori sangat baik), Buku 3 dari 91% (kategori sangat baik), dan Buku 4 dari 92% ( kategori sangat bagus). Di lapangan untuk skor tes observasi pada Buku 1 dari 95% (kategori sangat baik), Buku 2 dari 95% (kategori sangat baik), Buku 3 dari 91% (kategori sangat baik), Buku 4 dari 95% (kategori sangat baik). Dari semua tahapan yang sudah dilakukan sehingga dapat disimpulkan bahwa buku cerita matematika dinyatakan valid, praktis, dan memiliki potensi efek bagi anak.Kata Kunci: buku cerita, matematika